Learning cultural literacy through creative practices in schools : cultural and multimodal approaches to meaning-making /: cultural and multimodal approaches to meaning-making. (2021) - Lähdesmäki, Tuuli; Baranova, Jūratė; Ylönen, Susanne C; Koistinen, Aino-Kaisa; Mäkinen, Katja; Juškiene, Vaiva; Zaleskiene, Irena
No abstract available